The Influence Of Gender Diversity Of The Board Of Directors On Risk Disclosure in Indonesia - Chandra, Budi; Theresia, Theresia; Ivone, Ivone (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
This research aims to analyze the influence of gender diversity, female directors and company age on risk disclosure in companies listed on the Indonesia Stock Exchange. Other variables used are gender diversity, female directors and company age. The population of this research is several companies registered on the IDX for the 2018-2022 period with a total of 347 data. The analytical method used in this research is panel data regression. The research results show that there is a negative correlation between GDBL, GDSH, GAGE and risk disclosure, but there is also a negative correlation between ROA and risk disclosure with GAGE moderation which is consistent with the research results of Kristina and Wiratmaja (2018) who have found evidence that shows there is a positive correlation between ROA with risk disclosure with GDFP moderation. Furthermore, there is no correlation between GDFP, ROA, LEV. with risk disclosure, but there is also no correlation between LEVE and risk disclosure with moderation of GDFP and GAGE which is inconsistent with the research results of Wulandari and Wirakusuma (2017) which state that LEVE has a positive effect on risk disclosure with moderation of GDFP and GAGE.